Rural Crime and Community Safety - Ceccato, Vania A (Routledge Studies in Crime and Society, 2016)
Crime is often perceived as an urban issue rather than a problem that occurs in rural areas, but how far is this view tenable? This book explores the relationship between crime and community in rural areas and addresses the notion of safety as part of the community dynamics in such areas. Rural Crime and Community Safety makes a significant contribution to crime science and integrates a range of theories to understand patterns of crime and perceived safety in rural contexts. Based on a wealth of original research, Ceccato combines spatial methods with qualitative analysis to examine, in detail, farm and wildlife crime, youth related crimes and gendered violence in rural settings. Making the most of the expanding field of Criminology and of the growing professional inquiry into crime and crime prevention in rural areas; rural development; and the social sustainability of rural areas, this book builds a bridge by connecting Criminology and Human Geography. This book will be suitable for academics, students and practitioners in the fields of criminology, community safety, rural studies, rural development and gender studies.